Lung Adenocarcinoma Exhibiting Thanatosomes (Hyaline Bodies), Cytoplasmic Clearing, and Nuclear Pleomorphism, with a KRAS Mutation - Mitsuhiro Tachibana; Yutaro Ito; Ryo Fujikawa; Kei Tsukamoto; Masahiro Uehara; Jun Kobayashi; Takuo Hayashi (Diagnostics)
Since epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors were introduced in 2004, various driver gene mutations have been identified in non-small cell lung cancer, particularly adenocarcinoma, where mutations are typically mutually exclusive. EGFR and Kirsten rat sarcoma viral oncogene (KRAS) mutations are most prevalent in Japan, with routine testing now standard. However, hematoxylin and eosin staining often fails to detect mutations, except in cases such as ALK fusion lung cancer. We report a 76-year-old non-smoking Japanese woman diagnosed with adenocarcinoma confirmed as KRAS G12D/S-positive. Histological features, including thanatosomes (hyaline globules), nuclear pleomorphism, and cytoplasmic clearing, may aid in identifying mutations. Numerous thanatosomes were identified, some containing nuclear dust. Thanatosomes revealed periodic acid–Schiff reactivity with diastase resistance, fuchsinophilia with Masson’s trichrome stain, and dark blue-black color with Mallory’s PTAH stain. This is the first report linking thanatosomes in KRAS-mutant pulmonary adenocarcinoma to apoptosis via cleaved caspase-3 staining.